114 Peripheral blood mononuclear cell expression of the stabilizing RNA-binding protein HUR is associated with incidence and extent of human atherosclerotic cardiovascular disease. (May 2019) - Vlachogiannis, Nikolaos; Sachse, Marco; Mareti, Alexia; Georgiopoulos, Georgios; Sopova, Kateryna; Tual-Chalot, Simon; Kritsioti, Chrysa; Laina, Aggeliki; Kontogiannis, Christos; Zaman, Azfar; Spyridopoulos, Ioakim; Gatsiou, Aikaterini; et al.
Abstract : Introduction: Human Antigen R (HuR) is a stabilizing RNA-binding protein that regulates the expression of several pro-inflammatory molecules. However, its regulation in human atherosclerotic cardiovascular disease remains unknown. Herein, we sought to determine the association of peripheral blood mononuclear cell HuR expression with established markers of increased cardiovascular risk and atherosclerosis burden in patients with subclinical or clinically overt coronary artery disease (CAD). Methods: HuR mRNA expression was measured in peripheral blood mononuclear cells derived from 289 patients with stable CAD or acute myocardial infarction (AMI) and 373 individuals without clinically overt cardiovascular disease (CVD). Structural and functional vascular measurements including intima-media thickness (IMT) and number of atheromatous plaques by carotid and femoral artery ultrasonophaphy, markers of arterial wave reflections by pulse wave analysis and pulse wave velocity were used as surrogate markers of subclinical CVD. The number of angiographically confirmed diseased coronary arteries (>50% stenosis) was used to assess the extent of CAD. Results: HuR mRNA expression was significantly increased in patients with CAD (both stable and AMI) compared to controls (p=0.039). Subgroup analysis revealed that STEMI patients (n=107) had increased levels of HuR expression compared to NSTEMI (n=49, p=0.03). Among patients with stable CAD (n=133), high HuR expression was independently associated with the number of diseased coronary arteries (OR=1.35 for 1-SD increase in HuR, 95% CI 1.07–1.72, p=0.012), as well as with reduced ejection fraction (EF<45%, OR=1.32 per 1-SD increase, 95% CI 1.05–1.85, p=0.024). Among individuals without CVD, high HuR was associated with lower HDL levels (adjusted beta=-5.2 mg/dl for highest versus lowest quartile, p=0.03) and higher diastolic blood pressure (adjusted beta=3.6 mmHg, p=0.007), while, after adjustment for traditional cardiovascular risk factors, HuR levels in individuals without CVD were independently associated with increased IMT in the common carotid artery (mean increase 6.2% for highest versus lowest quartile, p=0.019). Conclusion: HuR expression is associated with early subclinical arterial disease in individuals without clinically overt CVD and with the presence and severity of cardiac and vascular dysfunction in patients with clinically overt CAD. These findings imply a clinical role of the HuR pathway in cardiovascular disease and warrant further investigation. Conflict of Interest: none